KECEMASAN GURU-GURU BAHASA INGGRIS DALAM MENGAJAR MATA PELAJARAN BAHASA INGGRIS DI SMA - Setya Resmini; Evie Kareviati; Yugafiati Rasi (IKIP SILIWANGI, 2020)
Teachers apply the theories in the campus into reality in the classroom. Unfortunately, they face the truth that some students feel anxious in learning English. The language anxiety makes the students can not explore their performance. It becomes teachers’ anxiety when the students deal with the feeling. The aim of the community service is to discuss and brainstorm between lecturers as experts and teachers as practicians. It aims to analyze the teachers’ anxiety in teaching English. The community service is held in Cililin in January 2020. The community service is started by explaining Language Anxiety. Then, the lecturers explain about Coping Strategies. Then, they explain about teaching English based on Industrial Era 4.0 through cultural literation of Cililin. It is closed by the QnA session. Some of the lecturers by the committee. The result is the teacher's anxiety level is quite high. By joining the event of community service, the teachers can decrease their anxiety because the lecturers can give several advice and solutions. The conclusion is the anxiety level of English teachers in senior high schools can be decreased when they discuss with the lecturers in a community service event.